“Karl und Martin”: Is there any influence of Martin Luther on Karl Marx? (Ágora Journal, 2026)
This article aims to discuss whether there is any influence of the reformer Martin Luther on Karl Marx's economic thought, including debating whether Marx can or cannot be considered a “non-practicing Lutheran”, since he was baptized and confirmed. Precisely because he was confirmed at the age of 16, Marx had to study Luther's Small Catechism, where the reformer's explanation of the commandments of “thou shalt not kill” and “thou shalt not steal” may have had a strong influence on Marx for the later development of his concept of exploitation. The article aims to analyze Luther's three specific works on economics, to see clues to their influence on Marx, especially since Luther is cited in Capital.
Keywords: Marx; Luther; Economy.